Media Online Sebagai Pemenuh Kebutuhan Informasi yang Tepat Bukan yang Cepat - Rokibullah Rokibullah (Jurnal Indonesia Sosial Sains, 2022)
Information is a very important consumption for people's daily life. The information obtained must also be in accordance with the data or in accordance with existing facts. Such data can be in the form of facts, events, news, phenomena, or the like which can be processed / processed based on certain procedures which then become information. Information can be obtained from various existing media sources, including from the internet or online media. In online media, in addition to having speed in accessing information, it must also be accurate or accurate in the process of conveying the information. So that with the speed and accuracy that online media will have more qualified credibility, which is not careless in conveying and disseminating information or news. In the delivery of information, online media or related parties, including journalists, must also comply with matters or provisions that do not violate the code of ethics and do not violate the Law (UU) on the Press Number 40 of 1999. this, online media and related parties cannot play as they wish. For the sake of increasing ratings, online media cannot carelessly publish news or information, by prioritizing speed over accuracy or accuracy. Online media should be a spirit for the public to raise awareness and play a role in public life, by considering its limitations and strengths. So that with this, good quality and journalism will be built in the media. Therefore, all related parties are expected to be able and wiser in utilizing or transacting via the internet, especially in the world of journalism.